Implementation Of Accountability And Transparency In The Financial Management Of Sinar Mulya Village, Banyumas Sub-District - Dini Seviyawati; Khairudin Khairudin; Riswan Riswan (Cita konsultindo, 2024)
Accountability and transparency are the processes by which the government reports and shows the public the actions it has taken. Accountability can be used to see whether all activities carried out have been carried out transparently or not. The research conducted by this author aims to see how the implementation of accountability and transparency in financial management in Sinar Mulya Village is based on the regulations of Permendagri No. 20/2018. This research uses a qualitative method based on field studies. Data was obtained through direct interviews with the village head, village secretary, village treasurer, and several communities in Sinar Mulya Village. The results of this study found that although the transparency of village financial management is still not good, the implementation of financial management accountability is quite good. This study suggests hiring a technology expert to handle the village website efficiently or hiring people who have specialized knowledge in technology and information.